1989
DOI: 10.3758/bf03208052
|View full text |Cite
|
Sign up to set email alerts
|

Shifting of attentional focus within and about a visual display

Abstract: If several positions must be attended in a large visual display, does the efficiency of performance vary as a function of the display distance between these to-be-attended positions? Two previous experiments (Podgorny & Shepard, 1983;Shaw, 1978) gave conflicting answers. In the present experiments, eight-letter circular displays were briefly presented. On each trial one, two, or three positions of the display were cued or preeued. The number of noncued display positions intervening between the cued locations v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 38 publications
8
55
0
Order By: Relevance
“…However, the distance effects may have to do with processes involved in screening out the distractors rather than the processes involved in computing the relation between the targets. Eriksen and Webb (1989) cued two positions in a multielement display in a task that did not require computing spatial relations between the cued positions and found that RT decreased as the distance between the cues increased. Perhaps it is easier to ignore distractors if several of them can be grouped together (Duncan & Humphreys, 1989;Humphreys & Miiller, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the distance effects may have to do with processes involved in screening out the distractors rather than the processes involved in computing the relation between the targets. Eriksen and Webb (1989) cued two positions in a multielement display in a task that did not require computing spatial relations between the cued positions and found that RT decreased as the distance between the cues increased. Perhaps it is easier to ignore distractors if several of them can be grouped together (Duncan & Humphreys, 1989;Humphreys & Miiller, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…If attention could be focused so that only two objects impinge on the model at one time, then above and below could be assigned unambiguously. However, it is not clear whether attention can be directed simultaneously to two different locations; the issue is currently controversial (see, e.g., Castillo & Umilta, 1992;Eriksen & St. James, 1986;Eriksen & Webb, 1989;Eriksen & Yeh, 1985;Posner, 1980;Shaw, 1978). The evidence that attention can be split comes mostly from experiments that cue the locations of single items (e.g., Castillo & Umilta, 1992).…”
Section: Hummel and Biederman (1992)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a reanalysis of their experiments and data (C. W. fails to support such a conclusion. Furthermore, subsequent research has strongly indicated that attention either shifts or indexes locations in the visual field in a discrete manner with the time required for shifts from one location to another to be independent of the distance between the locations (C. W. Eriksen & Webb, 1989;KWak, Dagenbach, & Egeth, 1991;Sagi & Julesz, 1985).…”
Section: Serial Versus Parallel Processing Of Targetsmentioning
confidence: 99%
“…Attempts to characterize attention shifts have used five basic paradigms, all of which involve spatial cues: (a) simple reaction times (RTs; e.g., Hughes & Zimba, 1985, 1987Posner et al, 1978;Posner et al, 1980;Remington & Pierce, 1984;Rizzolatti, Riggio, Dascola, & Umilta, 1987;Shulman, Remington, & McLean, 1979;Shulman, Wilson, & Sheehy, 1985), (b) choice RTs (e.g., Colegate, Hoffman, & Eriksen, 1973;Egly & Homa, 1991;Eriksen & Hoffman, 1972, 1973, 1974Eriksen & Webb, 1989;Hoffman, 1975;Jonides, 1980Jonides, , 1983Klein, 1994;Musseler, 1994;Podgory & Shepard, 1983;Posner et al, 1980, Experiments 3 and 4;Shaw, 1978;Tsal, 1983), (c) discrimination (e.g., Cheal & Lyon, 1989;Cheal, Lyon, & Gottlob, 1994;LaBerge & Brown, 1986;Lyon, 1990), (d) partial report (e.g., Averbach & Coriell, 1961;Sperling, 1960; also see Coltheart, 1980, for reviews), and (e) attention gating (e.g., Reeves & Sperling, 1986;Sperling & Reeves, 1980;Sperling & Weichselgartner, 1995;Weichselgartner & Sperling, 1987). Major theories of attention shifts-spotlight (e.g., Posner et al, 1980), zoom lens (e.g., Eriksen & Yeh, 1985), gradient (e.g., …”
Section: Principal Paradigms For Investigating the Mechanisms Of Covementioning
confidence: 99%